Population genetic characteristics of Aedes aegypti in 2019 and 2020 under the distinct circumstances of dengue outbreak and the COVID-19 pandemic in Yunnan Province, China - Wang, Ge; Gao, Jian; Ma, Zu; Liu, Yuan; Wang, Ming; Xing, Dan; Li, Chunxiao; Guo, Xiaoxia; Zhao, Teng; Jiang, Yuting; Dong, Yande; Zhang, Hengduan; et al. (Frontiers in Genetics, 2023)
Since Aedes aegypti invaded Yunnan Province in 2002, its total population has continued to expand. There are few studies on the population genetic characteristics of Ae. aegypti in Yunnan Province under different levels of human intervention. This study mainly used two common types of molecular markers to analyze the genetic characteristics of Ae. aegypti, revealing the influence of different input, prevention and control pressures on the genetic diversity and structure of this species. Understanding the genetic characteristics of Ae. aegypti populations and clarifying the diversity, spread status, and source of invasion are essential for the prevention, control and elimination of this disease vector. We analyzed the genetic diversity and genetic structure of 22 populations sampled in Yunnan Province in 2019 and 17 populations sampled in 2020 through nine microsatellite loci and COI and ND4 fragments of mitochondrial DNA. Analysis of Ae. aegypti populations in 2019 and 2020 based on microsatellite markers revealed 67 and 72 alleles, respectively. The average allelic richness of the populations in 2019 was 3.659, while that in 2020 was 3.965. The average polymorphic information content (PIC) values were 0.546 and 0.545, respectively, showing high polymorphism. The average observed heterozygosity of the 2019 and 2020 populations was 0.538 and 0.514, respectively, and the expected average heterozygosity was 0.517 and 0.519, showing high genetic diversity in all mosquito populations. The populations sampled in 2019 had 10 COI haplotypes and 17 ND4 haplotypes. 20 COI haplotypes were found in the populations sampled in 2020, and 24 ND4 haplotypes were obtained. Cluster analyses and a network diagram showed that the populations of Ae. aegypti in Yunnan Province could be divided into two clusters. However, under different input pressures, the source populations of the 2019 and 2020 populations changed. Correlation analysis indicated that population geographic distance and genetic distance had a moderately significant correlation in 2019 and 2020. Ae. aegypti in Yunnan Province maintains a high degree of genetic diversity and continues to expand. Human interference is one reason for the changes in the genetic characteristics of this disease vector.